Introductory Thoughts about Peace, Politics and Religion - Jeffrey Haynes (Religions, 2020)
Recent years have seen a growing literature on the interactions between peace, politics and religion, including their diverse and often complex relationships. Underpinning this literature is an increase, more generally, in scholarly and policy interest in connections between religion and politics. The context is that over the last three decades, religion has made a remarkable return to prominence in various academic literatures, including sociology, political science and international relations. This was a surprise to many social scientists and confounded the expectations of both secularization theorists and secularists. In addition, religion retained a strong, some say growing, significance as a core source of identity for billions of people around the world. Numerous religious leaders and faith-based organizations are important carriers and focal points of religious ideas, playing an important role in many countries, both developed and developing, as well as internationally, including at the United Nations and to a lesser, although still notable extent, in the European Union and other regional organizations. This introductory article examines interactions between religious entities in relation to peace and conflict and sets the scene for the articles comprising this volume.